ANALISIS EFEKTIFITAS SISTEM PENGENDALIAN INTERNAL PIUTANG PADA RSUP DR. WAHIDIN SUDIROHUSODO - Nursuriyawati Nursuriyawati; Mursalim Mursalim; Muhammad Su'un (Bongaya Journal for Research in Accounting (BJRA), 2020)
This Research aims to determine the effectiveness of the internal control system against receivables on RSUP Dr Wahidin Sudirohusodo based on operational standards and procedures as well as the rules for managing BLU receivables. This type of research is qualitative research with a descriptive approach. The type of data in this study are primary data. While the data source of this research is a questionnaire. The population in this study were 7 fields related to the management of accounts receivable at RSUP Dr Wahidin Sudirohusodo. The technique used in sampling was judgment technique with a total of 42 people. The results of research indicate that the internal control system of receivables at RSUP Dr. Wahidin Sudirohusodo has been carried out in accordance with Operational Standards and Procedures but not yet in accordance with the rules for managing receivables BLU because the risk assessment component still has weaknesses in the internal control system of receivables due to inconsistencies found in the classification of the settlement of receivables. . The internal control system is a component of the controlling environment; risk assessment; control activities; information and communication; and supervision and monitoring fall into the quite effective category. The results of this study indicate that the internal control system of receivables at RSUP Dr. Wahidin Sudirohusodo has been carried out in accordance with Operational Standards and Procedures but not yet in accordance with the rules for managing receivables BLU because the risk assessment component still has weaknesses in the internal control system of receivables due to inconsistencies found in the classification of the settlement of receivables. The internal control system is a component of the controlling environment; risk assessment; control activities; information and communication; and supervision and monitoring fall into the quite effective category.